ATTITUDES AND EXPECTATIONS TOWARD ARTIFICIAL INTELLIGENCE TOOLS IN LEARNING AMONG POSTGRADUATE STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2025 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe attitudes and expectations toward the use of artificial intelligence (AI) tools in learning and to analyze related factors among postgraduate students at Hanoi Medical University in 2025.Methods: A cross-sectional study was conducted among 380 postgraduate students using a self-administered questionnaire. Data were collected online and analyzed using STATA 17.0.Results: Overall, 73.02% of participants perceived the use of AI in learning as necessary or very necessary, reflecting positive attitudes and high expectations toward AI. ChatGPT was the most commonly used AI tool. A significant association was found between the level of AI knowledge and attitudes and expectations toward AI use in learning (p < 0.05), while no significant associations were observed with gender, year of study, or information technology skills.Conclusions: Postgraduate students demonstrated positive attitudes and high expectations toward the use of AI for learning purposes. Integrating structured AI training into postgraduate medical education programs is necessary to meet practical needs and improve the quality of medical education.
Keywords: artificial intelligence; ChatGPT; medical education; postgraduate students; attitudes and expectations.